Stress vulnerability in Medical Health Care Professionals of Pakistan during the COVID- 19 pandemic - Ashfaq Ahmad Shah Bukhari; Saman Tauqir; Muhammad Mansoor Tariq; Umair Wadood; Rashid Mahmood; Saadia anwar; Muhammad Haidar Zaman (Al-Qanṭara, 2022)
Abstract Background: The Novel Corona Virus SARS-CoV-2 originated from China, it has crossed borders and has infected countries around the globe. The virus has attracted massive public attention; media reporting across borders and has kept the world informed about this public health emergency. Pandemics like these can be a source of high stress in health care professionals due to heavy workload, long working hours, and limited resources. So, it is of immense importance to check the mental health of our frontline warriors. This study attempts to assess stress vulnerability in the medical sector of Pakistan during the COVID-19 pandemic. Method: An observational online survey was conducted using the stress vulnerability questionnaire via convenience sampling technique. A total of 329 responses were received. Results and Conclusion: A total of 329 responses were recorded, males (45.3%) and females (54.7%). All the participants were above 15 years of age and of Pakistani origin. The study included participants related to medical sector i.e. general practitioners (5.8%), consultants (4.9%), dentists (12.5%), residents/ Interns (12.2%), undergraduate medical students (51.7%), Basic sciences faculty (7%), clinical faculty, and medical researchers (6.1%). Different parameters related to their daily life were analyzed to interpret the psychiatric condition of these subjects. Our study showed that several frontline warriors of Pakistan were vulnerable to stress and depression during the COVID-19 pandemic. Hence, our government should take immediate measures to reduce their burden and ensure that the mental health of health care professionals is regularly monitored. Key Words: COVID-19, Stress vulnerability, Medical Sector, Health care